Android for Work - Karch, Marziah (Apress, 2012)
This book was written mainly for the mobile office worker who wants to check work e-mail and maybe tether Wi-Fi with a laptop while still getting the most out of the fun features in Android. You don’t need to be a programmer or computer whiz to use this book, and there should hopefully be enough goodies here for both the new and veteran Android owner. Android is still innovating very rapidly, both from operating system (OS) upgrades and phone vendor modifications, and new Android-based phones are being released all the time. This book was written mainly using a Google Nexus One running Android 2.1 and 2.2. The Nexus One model was both powerful and carrier neutral, so it seemed an ideal choice. I’ve tried to make note of any variations between phones, OS versions, and carriers, but there are going to be times where what I describe is not quite the same as what you see on your screen. In most cases, these should be minor differences. It’s been very exciting to see Android grow as I wrote this, and it will be even more exciting to see how it does in the future. I hope this book serves as a useful reference to getting the most out of your Android phone.